FRI0187 IMMUNOGENICITY OF 23-VALENT POLYSACCHARIDE PNEUMOCOCCAL VACCINE IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS: EFFECT OF BIOLOGIC THERAPY ON THE VACCINAL RESPONSE. (2nd June 2020) - Tarasova, G.; Belov, B.; Cherkasova, M.; Solovyev, S.; Aseeva, E.; Reshetnyak, T.; Popkova, T.
Abstract : Background: Vaccination with 23-valent polysaccharide pneumococcal vaccine (PPV-23) in systemic lupus erythematosus (SLE) provides the prevention of severe respiratory infections in patients receiving immunosuppressive therapy. The importance of this vaccination significantly increases before and during treatment with biologics. Objectives: The aim of the study was to evaluate the immunogenicity of PPV-23 in SLE patients. Methods: The study included 52 patients with SLE, including 44 women and 8 men, aged 19 to 68 years. The duration of the disease varied from 9 months to 39 years. At the time of vaccination 7 patients had high, 10 – moderate, 30 – low activity of the disease according to SLEDAI 2K, and 5 had remission. 50 patients received glucocorticoids (GC) 5-30 mg/day equivalent to prednisone, 39 – hydroxychloroquine (GCH), 29 – cytostatics (CS), 20 – biologics: 10 – rituximab (RTM), 10 – belimumab (BLM). 1 dose (0.5 ml) of PPV23 was administered subcutaneously. During the visits, standard clinical and laboratory tests were performed, and the level of antibodies (Ab) to S.pneumoniae in blood serum was determined (VaccZymeTMPCPIg 2 kits – The Binding Site Ltd, Birmingham, UK). Results: In 1-2 months after the vaccination 78.7% of patients had a significant (more than 2 times compared to baseline) increase in the concentration of Ab to the pneumococcal cell wall polysaccharides. A year after vaccination, 61.5% of patients ("responders") had a significant increase in the concentration of anti-pneumococcal Ab. 20 (38.5%) of 52 patients were considered "non-responders". Median concentration of anti-pneumococcal Ab was 67[42.6; 105.8] mg/l at visit 1 (initially), 405[143.5; 468.4] mg/l at visit 2 (in 1-2 months), 166.9[77.5; 377.4] mg/l at visit 3 (in 12 months). There were clear differences in the degree of the vaccinal response depending on the therapy: in 20 patients receiving biologics full vaccinal response was achieved significantly less frequently than in patients who did not receive these drugs (40% and 75%, respectively), p=0.02. There were no obvious differences in the vaccinal response during treatment with RTM and BLM (40% of responders in both groups). The vaccinal response significantly decreased during treatment with biologics in combination with GC+/ - GCH (50% of responders). The lowest vaccinal response was observed in patients receiving biologics in combination with GC and CS + / - GCH (33.3% of responders). The analysis of the degree of the vaccinal response depending on the timing of vaccination and the time of biologics infusion was carried out. In the first group (n=6), vaccination was carried out at the optimal time in accordance with the recommendations of EULAR (2020). In the second group (n=14) vaccination was carried out in suboptimal time: during regular treatment with BLM (n=6), 1 week before the next introduction of RTM (n=2), 3-5 months after the last introduction of RTM (5), 1 week before the next introduction of RTM (n=1), 20 days after the BLM termination (n=1). In the first group with optimal vaccination terms, the number of responders was 66.7%, in the second group with suboptimal terms – 28.6%, p=0.27. Conclusion: Sufficient immunogenicity of PPV-23 was shown in SLE patients receiving immunosuppressive therapy. The negative impact of biologics on the vaccinal response was confirmed, especially if the vaccination was not performed at the optimal time in relation to the infusion of the drug or during monthly administration of BLM. If optimal vaccination terms are maintained during the treatment with or initiation of biologics (6 months after the last administration of RTM and 1 month before the next (or first) administration of RTM, 4 months after the last and 1 month before the next (or first) administration of BLM), the number of responders increases significantly. The lowest vaccinal response was obtained in patients receiving combined immunosuppressive therapy with biologics + GC+CS. Disclosure of Interests: None declared